General practitioners and palliative care practices: a better knowledge of specific services is still needed - Daouda Niaré; Guillaume Robert; Auriane Rocquevieille; Loïc De Geyer; Maguy Frin; Sophie Pennec; Thomas Hanslik; Thierry Blanchon; Louise Rossignol; Vincent Morel (BMC, 2024)
Abstract Background France allows deep sedation for pain relief, but not for euthanasia. In anticipation of an increase in home-based palliative care, the role of general practitioners is central to the design of outpatient palliative care services. This study aimed to describe the knowledge, attitudes, and practices of general practitioners in mainland France regarding palliative and end of life care. Methods This was a national descriptive cross-sectional study within the Sentinelles network. Self-report questionnaires were distributed to general practitioners between November 2020 and November 2021. A descriptive analysis was carried out. Results Out of the 123 participating general practitioners, 84% had received academic training in palliative care (n = 104). While a significant majority (69%) expressed comfort in pain management, only a quarter (25%) declared that they were competent at indicating deep and continuous sedation for pain relief. Awareness of outpatient palliative care facilities close to their place of practice such as hospitalization at home was over 97% (n = 117/120). Awareness of hospital facilities, including identified palliative care beds on hospital wards and palliative care units, was lower (75% (n = 59/79) and 86% (n = 86/100), respectively). Conclusions Our results suggest that French general practitioners are reasonably aware of palliative care resources available. However, there is room for improvement, particularly in understanding hospital-based facilities. Furthermore, a quarter of the general practitioners expressed discomfort with deep and continuous sedation for pain relief, highlighting the need for increased training in this specific aspect of palliative and end of life care.